Analysis of Teaching Speaking Through Audio-Visual Methods at Jitjongrak School, Krabi, Thailand - Rossa, Angeli Shela; Imaniah, Ikhfi; Suhendar, Asep (JP (Jurnal Pendidikan) : Teori dan Praktik, 2025)
Speaking skill is essential in English language learning but remains challenging for primary school learners, especially in multicultural and multilingual contexts. This qualitative descriptive study explores an English teacher’s perspective on the use of audiovisual media to enhance speaking skills at a primary school in Southern Thailand. Data were collected through online semi-structured interviews and analyzed using a rigorous thematic analysis process involving open, axial, and selective coding, validated by peer debriefing. Findings indicate that authentic audiovisual materials promote interactive and contextual learning, improve vocabulary, pronunciation, and sentence structure, and increase student confidence and participation. The study addresses a significant research gap in audiovisual media use in young learners within under-researched multilingual settings, offering novel insights into effective teaching strategies and multimedia scaffolding theories. This research provides practical implications for educators aiming to integrate technology to improve speaking proficiency.